PENINGKATAN KEAKTIFAN ORGANISASI PEMUDA MELALUI PELATIHAN DASAR KEPEMIMPINAN (PROGRAM PENGABDIAN DI DESA REJASA, KECAMATAN PENEBEL, KABUPATEN TABANAN) - I Putu Fery Karyada (JURNAL SEWAKA BHAKTI, 2018)
Youth organization is a place to develop potential and leadership. However, many young people do not understand the role, function and benefits in organization then couse lack of their activity. In addition, the lack awareness of mutual cooperation (gotong royong), difficulty in teamwork, and the occurrence internal conflicts led to the weakness of youth organizations in Rejasa. The purpose of leadership training is to increase awareness and activeness of youth in organizing. The participants are 92 people who are representatives from four Banjar Dinas Desa Rejasa. The training was held for two days and took place in Balai Serba Guna Rejasa. The methods used are lectures, discussions, and leadership games. In addition, participants also introduced to Yoga activities. After the leadership training, participants are more aware of the function and role in organizing. Familiarity and cohesiveness among participants can also be improved. With yoga activities, participants can also maintain physical and spiritual health. Keyword: Generasi Muda, Organisasi Pemuda, Pelatihan Kepemimpinan.